"When you are injected, the baby is protected:" Assessing the acceptability of a maternal Tdap vaccine based on mothers' knowledge, attitudes, and beliefs of pertussis and vaccinations in Lusaka, Zambia. Issue 21 (17th May 2018) - Larson Williams, Anna; McCloskey, Lois; Mwale, Magdalene; Mwananyanda, Lawrence; Murray, Kenya; Herman, Augusta R.; Thea, Donald M.; MacLeod, William B.; Gill, Christopher J.
Highlights: Qualitative data from Zambia demonstrates that maternal vaccine hesitancy is low. Limited knowledge of vaccines and pertussis did not reduce vaccine acceptability. Zambian mothers support a maternal Tdap vaccine to protect infant health. Community rumors and partner involvement impact mothers' healthcare decisions. Abstract: Introduction: Severe and fatal pertussis infections are concentrated among infants who are too young to be protected through routine vaccinations. Maternal Tdap (mTdap), which is now the standard of care in the US and UK, is considered to be the most effective way to address this gap in preventative care. Little is known about how pregnant women in low-resource settings might view mTdap. To inform strategies for mTdap implementation in these contexts, public health researchers sought to understand knowledge, attitudes, and beliefs toward pertussis and maternal vaccines and assess the barriers to vaccine acceptance. Methods: We conducted focus group discussions (FGDs) among mothers who participated in a longitudinal birth cohort study at the Chawama primary health center in Lusaka, Zambia. Since SAMIPS was not a clinical trial, but instead an observational cohort study, registration on clinicaltrials.gov was not required. Trained interviewers conducted the FGDs in January 2016 using a semi-structured interview guide, exploring participants' knowledge, attitudes and beliefs toward pertussis and vaccines. We analyzed the transcripts using Nvivo v.11 software. Results: Fifty mothers participated across 7 FGDs. Mothers had limited knowledge of pertussis and vaccines, yet expressed generally positive views of vaccinating themselves and their children. Participants conveyed very little vaccine hesitancy around maternal vaccinations, and discussed how they could protect their children's health. Mothers also highlighted barriers and facilitators to vaccine uptake, which included partner involvement, feelings of maternal authority over healthcare decision-making, and community rumors about Western medicine. Conclusion: Mothers viewed vaccinations as an important method to keep their children healthy, despite cultural myths and misconceptions about pertussis and vaccines. FGD results suggest that vaccine acceptability is high in Zambia, which is a critical factor to vaccine uptake. A strategy addressing myths and misconceptions should be prioritized if and when mTdap is introduced across low-resource settings.